2015
DOI: 10.3168/jds.2014-8875
|View full text |Cite
|
Sign up to set email alerts
|

The effect of buffering dairy cow diets with limestone, calcareous marine algae, or sodium bicarbonate on ruminal pH profiles, production responses, and rumen fermentation

Abstract: Six ruminally cannulated Holstein cows were used to evaluate the effect of 2 dietary buffers on rumen pH, milk production, milk composition, and rumen fermentation parameters. A high concentrate total mixed ration [35.2% forage dry matter (DM)], formulated to be potentially acidotic, was used to construct 3 dietary treatments in which calcareous marine algae (calcified remains of the seaweed Lithothamnium calcareum) was compared with limestone (control) and sodium bicarbonate plus limestone. One basal diet was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
61
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 29 publications
(66 reference statements)
15
61
0
12
Order By: Relevance
“…In agreement with the above reports, higher VFA concentrations were observed with BC supplementation in the current study. Acetate and propionate concentrations increased as well, which is also in agreement with previous studies of lactating cows . In addition, the present study revealed that butyrate concentrations and molar proportions were lower in the BC group compared with the control.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the above reports, higher VFA concentrations were observed with BC supplementation in the current study. Acetate and propionate concentrations increased as well, which is also in agreement with previous studies of lactating cows . In addition, the present study revealed that butyrate concentrations and molar proportions were lower in the BC group compared with the control.…”
Section: Discussionsupporting
confidence: 93%
“…Sodium bicarbonate has been used as a supplement in dairy cows for many years as a rumen buffer . Studies involving BC in the diet of dairy cows have shown that BC supplementation can help elevate ruminal pH by buffering and by increasing the liquid dilution rate from the rumen . Consistent with these findings, the present study also revealed that the supplementation with BC resulted in an increase in final pH.…”
Section: Discussionsupporting
confidence: 85%
“…Owing to the interactive effect of treatment and period (P = .005; Table 4; Figure 1), the difference between both groups was more pronounced at the end of the experimental period. Many researchers have proved that the dietary inclusion of Zeolite improves average of yield of dairy cows (Katsoulos et al 2006;Ilić et al 2011;Ural et al 2013;Cruywagen et al 2015). Generally, an increase in milk production can result from increased ruminal concentrations of propionate, increased postruminal digestion of starch, increased microbial protein synthesis, increased by-pass protein, or from a combination of these factors (Garcia-Lopez et al 1992;Katsoulos et al 2006).…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…The NaHCO3 could increase the buffering capacity and prevent acidosis in the rumen. It was reported that the rumen pH profile improved and a higher yield of milk and milk solids when NaHCO3 was supplemented to a high-concentrate diet [21]. Previous studies indicated that the addition of NaHCO3 and MgO to restricted-roughage rations for goats could increase the content of lactose and milk yield [22].…”
Section: Discussionmentioning
confidence: 99%